Design of parking system miniature based personal computer using Borland Delphi 6.0 - Endi Permata; Mustofa Abi Hamid; Rian Raina Pertiwi (Department of Electrical Engineering Education, Faculty of Teacher Training and Education, 2018)
This research aims to create a miniature system for parking using Borland Delphi 6.0 software. The output data in the form of an analog optical sensors, so that the computer can read and manipulate data, then the data is converted to digital data by means of the output from the optical sensors sent to PPI 8255 which served to transform analog signals into a digital signals. The entire system is con-trolled entirely by computer through the PPI 8255 by Program Borland Delphi 6.0